2016
DOI: 10.3201/eid2208.151993
|View full text |Cite
|
Sign up to set email alerts
|

Probable Rabies Virus Transmission through Organ Transplantation, China, 2015

Abstract: Implementation of an effective regulatory system for testing donors would decrease the occurrence of donor-derived infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…This is surprising, as there are ample examples that the transmission of pathogenic viruses, albeit commonly rare, can occur. Prominent examples in renal transplantation are West Nile virus [5], lymphocytic choriomeningitis virus [6], human gammaherpesvirus 8 [7], and rabies lyssavirus [8]. Analyses of the virome thus far have focused solely on the kidney transplant recipients [9,10].…”
mentioning
confidence: 99%
“…This is surprising, as there are ample examples that the transmission of pathogenic viruses, albeit commonly rare, can occur. Prominent examples in renal transplantation are West Nile virus [5], lymphocytic choriomeningitis virus [6], human gammaherpesvirus 8 [7], and rabies lyssavirus [8]. Analyses of the virome thus far have focused solely on the kidney transplant recipients [9,10].…”
mentioning
confidence: 99%
“…In China, most human rabies cases can be ascribed to dog bites, and transmission via organ transplantation is rare (Tang et al, 2005 ). To our knowledge, a single rabies case via organ transplantation was reported in 2015 in Beijing (Zhou et al, 2016 ). In this study, RABV was identified in the saliva specimens from two kidney recipients at a hospital in Hunan, Changsha, using real time RT-PCR and NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of rabies transmission by corneal transplantation in 1979 (Houff et al, 1979 ), few cases ascribed to solid organ or vascular-tissue transplantation have been reported (Srinivasan et al, 2005 ; Vora et al, 2013 ). A transplantation-infectious case was reported in China in 2015 (Zhou et al, 2016 ). In January 2016, two kidney transplant recipients, who received organs from the same donor, presented with vomiting, abdominal pain, and right lower extremity weakness.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the ‘uncommon’ disease transmissions such as rabies have come with the use of organs from a previously healthy person who subsequently died with an undiagnosed/misdiagnosed neurologic event. Dozens of rabies virus transmissions to recipients via organs or tissues from donors with either undiagnosed or misdiagnosed inflammatory conditions of meningoencephalitis were reported [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%